(untitled) (International Journal of Engineering and Computer Science, 2014)
In today’s scenario, mobile computing has advanced to such an extent where the user has access to all the information on a single device. Today people are always moving with mobile devices like laptops, cell phones, tablets etc. Using the user’s geographic location, a lot of information related to the user of the mobile device can be collected. The knowledge of mobile user’s location can improve the class of services and applications that can be provided to the mobile device user. These classes of applications and services are termed as location based services. Location Based Service (LBS) is a kind of service that helps in getting the geographical location of the user and more useful information near to the user location. This location based information can be obtained in different terms such as position, vicinity, proximity, context, maps, routes, places etc. Our paper focuses on LBS in detail and identifies key components of LBS for providing this service to the user on the Android platform. It also explains the use and implementation of Google Maps and its APIs in getting various location based information on Android.